ANALISA SISTEM INFORMASI AKUNTANSI PENJUALAN TUNAI PADA THE GENTLEMAN BARBERSHOP DELTASARI MENGGUNAKAN APLIKASI MAJOO - Silvina Nur Fauzia; Rika Yuliastuti (STIE Mahardhika, 2021)
The analysis of cash sales accounting information systems at The Gentleman Barbershop aims to improve the cash payment system owned by the company to operate companies where these activities require information. An accounting information system is a system that plans, controls and operates a business. The Gentleman Barbershop is a business entity that is engaged in hair cutting services, recording transactions and previous financial reports using the Moka Application which always experiences errors and is not accurate, so I advise the owner to use the Majoo Application which is more accurate and safe. The complete entrepreneurial Majoo application for all solutions for all types of businesses that has many functions, the price of all entrepreneurial needs. Consists of online cashier, inventory, finance and accounting, employee attendance, CRM, and business analysis. The process starts from the beginning, namely analyzing the activities of The Gentleman Barbershop on the majoo application, then compiling data flow diagrams. The results of this study indicate that the majoo application is running well and is able to meet the information needs of The Gentleman Barbershop, collecting data using direct observation techniques at the salon, conducting interviews and conducting searches using literature.